EFEKTIVITAS MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM ASISTED INDIVIDUALITION UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN KEWARGANEGARAAN POKOK BAHASAN PERADILAN INTERNASIONAL DI KELAS XI SMA KATOLIK 1 KABANJAHE - Benni Faldo Girsang (Universitas Quality, 2018)
This study aims to determine: student learning outcomes after the implementation of cooperative learning model Team Type Asisted Individualition (TAI) to improve student learning outcomes in the subject of Civics Lesson subjects International Court of Justice.The location of this study is the students of class XI-IPS1 SMA Katolik 1 Kabanjahe which amounted to 31 students and the object of this study is the application of cooperative learning model Team Type Asisted Individualition to improve student learning outcomes on the subject of Civics International Court ofJustice. This type of research is Classroom Action Research (PTK). The instrument of data collection tool used is an objective test on the subject of International Judicature which has validated by validator.Based on the analysis of research improvements obtained by the average student grade completeness in classical 87.09% of students have complete learning and 12.91% of students not complete learning and TPK as a whole has reached 88.06%. And there is a significant difference of students' ability after the improvement of learning with the implementation of Cooperative Teaser Model Type Asisted Individualition (TAI). Keywords: Learning, Co-operative Team Type Asisted Individualition (TAI).